15-chain-rule

15-chain-rule - Math 1a The Chain Rule Fall, 2009...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 1a The Chain Rule Fall, 2009 & $ % Another Differentiation Rule The Chain Rule: Suppose F ( x ) = f ( g ( x )) (or F = f g ). Further sup- pose that g is differentiable at x and f is differentiable at g ( x ). Then F is differentiable at x and F ( x ) = f ( g ( x )) g ( x ) or dy dx = dy du du dx (where for the Leibniz notation expression were thinking of y = f ( u ) and u = g ( x )). This has consequences for all our previous differentiation techniques: 1 The derivative of y = ( f ( x ) ) n = u n : d dx ( f ( x ) ) n = n ( f ( x ) ) n- 1 f ( x ) or ( u n ) = nu n- 1 u (where n is any real number). 2 The derivative of an exponential function: d dx ( e u ) = e u u 3 The derivative of trigonometric functions: d dx sin( u ) = cos( u ) u and d dx cos( u ) =- sin( u ) u . Using these rules, compute the following derivatives. You need not simplify your final answer (except in problems 3 and 4). 1 Find y if y = ( x + 2) 3 . 2 Find dy dx if y = ( x 3 + 2) 3 . 3 Find dx dt if x = t 3 + 1 t 3- 1 . 4 Find dx dt if x = 1 + 2( t 3- 1)- 1 . 5 Find y if y = x 3 + x . 6 Find dy dx if y = 1 1 + x 2 7 Find dy dx if y = cos( x 2 ) + sin 2 ( x ). 8 Find y if y = e x 2- e 2 x . 9 Find y if y = x 3 ( x 2 + 1) 4 . 10 Find y if y = 1 ( x 2 + x ) 2 . 11 Find dy dx if y = ( x 2 + x )- 2 . 12 Find y if y = ( x 3 + 1) 3 x 2- x + 1 . 13 Find dy dx if y = 2 x 2 + x 2 2 4 ....
View Full Document

Page1 / 5

15-chain-rule - Math 1a The Chain Rule Fall, 2009...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online